Effects of physiotherapy in patients treated with chronic hemodialysis - Radojica Stolić; Branko Mihailović; Ivana Matijašević; Maša Jakšić (Биомедицинска истраживања, 2018)
Although physical activity is an important factor in prevention of many chronic, non-infectious diseases, it is rarely used as a regular procedure in dialysis patients. Despite the guidelines on good clinical practice, recommended physical exercise as a part of routine activities is implemented in a very small number of centers. Factors that contribute to sustainable exercise programs are the professional commitment of a multidisciplinary team consisting of physiotherapist, nephrologist, geriatrist, social worker, nurse, the incentive and encouragement of the entire dialysis staff for carrying out active exercise, as well as adequate physical space and equipment, with individualization for each patient in turn. Patients with end-stage kidney disease who are in the physical treatment program show significant functional improvements, especially those associated with the cardiovascular, respiratory and muscular system, as well as with the quality of life. There are no reports on serious injuries as a result of participation in the exercise program. This indicates that it is time for physical therapy to be included in the regular routine care procedure in hemodialysis patients. However, it is necessary to identify an optimal training regimen in accordance with the individual characteristics of each patient, in order to make it easier to apply the exercise program.
Keywords: physical activity; hemodialysis; intensity of exercise